Analisis Sentimen dan Emosi Publik pada Awal Pandemi COVID-19 Berdasarkan Data Twitter dengan Pendekatan Berbasis Leksikon - Yasinta Amalia Nur Jannah; Rindang Bangun Prasetyo (Seminar Nasional Official Statistics, 2022)
Coronavirus Disease 2019 (COVID-19) is infectious disease caused by Severe Acute Respiratory Illness Coronavirus. The spread of this virus is rapid and hard to control so in March 2020, World Health Organization declared COVID-19 as pandemic. COVID-19 pandemic has led negative impact on almost aspects of life. Start from social, economy, to public’s psychological state. During pandemic, outdoor activities are restricted. The number of unemployed increase. These thought to be background why people experiencing psychological disorders. Therefore, it’s necessary to monitor psychological state so public's mental health is maintained. The purpose of this study is to examine public sentiment and psychic as seen through public's emotional state during COVID-19 pandemic from March to July 2020. Twitter data is used as research data and then analyzed using sentiment and emotion analysis with lexicon-based approach. The results showed that negative sentiments were more widely expressed and fear was the emotion most felt by public. These can be used as recommendation for government to pay more attention public’s emotional state.